The magnet effect of price limits: an agent-based approach - Dong, Xinyue (2025)
In this paper, we study the magnet effect within the context of circuit breaker events that transpired in global stock markets during March 2020. Our analysis encompasses nine such events across six countries. Employing a time-distanced quadratic function to model trading activities leading up to limit hits, we observe a substantial acceleration in return movement and the convergence of traders’ behavior preceding limit hits. Furthermore, most circuit breaker events manifest a distinct reduction in trading volume and amplified market stability during this crucial phase. To gain deeper insights into the magnet effect, we employ an agent-based model of the stock market that incorporates price limits. Our model replicates the stylized facts associated with limit hit events and the magnet effect. Importantly, our simulation results closely align with empirical observations. We also emphasize the importance of market environment changes and shifts in traders’ behavior in influencing limit hit events and the magnet effect.